A multi-parameter evaluation of the neuroprotective and cognitive-enhancing effects of Origanum onites L. (Turkish Oregano) essential oil on scopolamine-induced amnestic rats - ŞENER, GÖKSEL; ÖZBEYLİ, DİLEK (My University, 2022)
Alzheimer\"s disease (AD) is a neurodegenerative disorder characterized by progressive deterioration of cognitive functions (dementia) and represents a growing public health concern since the population in the age groups at risk is increasing. The latter raises an urgent need to translate research findings in the basic brain and behavioral sciences into anti-AD drugs and disease-modifying therapies. Origanum onites (L.), also called Turkish oregano, is a perennial and herbaceous plant species grown for centuries for medicinal, cosmetic and culinary purposes. This is the first study to investigate the putative neuroprotective and pro-cognitive activities of O. onites essential oil (OOEO) against scopolamine-induced amnesia of AD-type in Wistar albino rats. The results of behavioral tests revealed that OOEO administration was able to significantly alleviate learning and memory impairments induced by scopolamine in vivo. The observed effects could be attributed to inhibition of acetylcholinesterase activity, attenuation of oxidative stress and prevention of neuronal apoptosis in the hippocampus and frontal cortex of AD rats. Modulation of pro-inflammatory enzymes, including cyclooxygenase-2, inducible nitric oxide synthase and myeloperoxidase, might further contribute to the neuroprotective properties of OEOO, as predicted by our in silico models. These findings offer novel insights into the therapeutic potential of OEOO in patients with AD.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Life Sciences; Natural Sciences; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); SİNİR BİLİMİ; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); NEUROSCIENCES; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); Endocrinology; Developmental Neuroscience; Endocrine and Autonomic Systems; Cellular and Molecular Neuroscience; Cognitive Neuroscience; General Neuroscience; Neuroscience (miscellaneous); Sensory Systems; Human-Computer Interaction; Endocrinology, Diabetes and Metabolism; Physical Sciences; Scopolamine-induced amnesia; Alzheimer's disease; Oxidative stress; Neuroinflammation; Apoptosis; Origanum onites; ALZHEIMERS-DISEASE; CYCLOOXYGENASE-2 EXPRESSION; MEMORY IMPAIRMENT; CARVACROL; EXTRACT; BRAIN; MYELOPEROXIDASE; PROTEINSPLUS; APOPTOSIS; DEFICITS; Alzheimer’s disease; Scopolamine-induced amnesia; Alzheimer’s disease; Oxidative stress; Neuroinfammation; Apoptosis; Origanum onites